Muslims and the Dilemma of Marriage Registration in Ghana: Perspectives from the Wala Muslim Community, Ghana - Yunus Dumbe; Eric Henry Yeboah; Mohammed Damba (E-Journal of Humanities, Arts and Social Sciences, 2023)
The Marriages Act, which regulates the various forms of marriages, outlines what constitutes a valid Muslim marriage in Ghana. It makes registration of Muslim marriages a requirement for its validity. Recently, a ‘Muslim Marriage and Divorce Bill, 2019 was addressed to the Office of the National Chief Imam, and various Muslim groups. This was largely informed by Muslims lack of patronage of the previous law regulating marriages and marriage registration in Ghana. The law was thus conceived with a view to get the inputs of the Muslim community into the new law to make it workable law. The central question that this study addresses is, why Muslims were not interested to patronize the previous legal expectations. The authors depended on oral sources and utilized qualitative approach in data analysis. Using the Wala Muslim community as the context, the article argue that Muslims are disinterested in the law because of the tension between secular law and Islamic Shari’ah principles. The tenets of the marriage registration law violate Islamic law, while aspects of it are impracticable. It is recommended that steps should be taken to educate the Muslim public on the need to register their marriages as well as empowering Imams to register marriages.